Nanocrystalline Zeolite Y: Synthesis and Heavy Metal Removal - Muhammad, Syaifullah; Munawar, Edi (Jurnal Rekayasa Kimia & Lingkungan, 2007)
Lead (Pb) and chromium (Cr) are common groundwater contaminants at industrial installation. Zeolites are widely use as an adsorbent in heavy metal removal. Nanocrystalline zeolite Y has been synthesised from a clear solution at 1500C by using aluminum isopropoxide (Al(OiPr)3 and Ludox LS as alumina and silica source, tetramethylammonium hydroxide (TMAOH) and tetramethyl ammonium bromide (TMABr) as first and second organic template, respectively. The products were characterised by X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) to identify the structure and particle sizes. After 48 hours synthesis time, nanocrystalline zeolite Y samples were obtained with approximately average particle sizes of 268 and 119 nm for one and two organic templates, respectively. The synthesized nanocrystalline zeolite Y was applied for some metal adsorption including Pb(II) and Cr(III) and the results show that the nano crystal samples have good performance. The removal efficiency for Pb and Cr could be up to 88.97% depending on the initial concentration and temperature. The adsorption isotherms of Cr and Pb were determined from the Langmuir and Freundlich equations. The equilibrium sorption capacities (Qe) from the Langmuir equation were 270.27 mg/g and 204.08 mg/g at 300C for Pb and Cr, respectively. Kinetic adsorption analysis of nanozeolite Y shows that the pseudo second order kinetics would be better for fitting the dynamic adsorption of both Cr and Pb cations.Key words: adsorption isotherms, kinetic adsorption analysis, nanocrystalline zeolite Y